Criminal Law Politics of Rechterlijk Pardon Concept (Comparative Study the New Criminal Code and Juvenile Justice System Law): (Comparative Study the New Criminal Code and Juvenile Justice System Law) - Firmansyah R, Adithya Tri; Rachman, Adhitya Alliyya; Yastisya, Annisa (Veteran Law Review, 2024)
The original Indonesian version of legal identity that was born from the soul of the Indonesian nation has been camouflaged by the hegemony of western legal thought that tends to be legalistic, formalistic and liberal in spirit. Therefore, it is time to purify the national legal identity by reforming the law. One form of legal reform is carried out by the state through the reform of criminal law, namely the New Criminal Code which regulates the concept of judge forgiveness (Rechterlijk Pardon) to undermine the character of colonial legacy criminal law which is rigid and not in accordance with the legal needs of society. On that basis, this research aims to review and analyze the comparison of the regulation of the concept of Rechterlijk Pardon in the Criminal Code and the SPPA Law which also regulates Rechterlijk Pardon and analyze the political construction of criminal law in updating the regulation of Rechterlijk Pardon in the New Criminal Code. This research is a normative legal research (doctrinal). The results of this study indicate that Article 70 of the SPPA Law provides options for judges with two things, namely not imposing punishment or imposing measures. Meanwhile, the concept of Rechterlijk Pardon in Article 54 paragraph (2) of the New Criminal Code is that the judge can actually consider not imposing either punishment or action, which of course shows a difference. Furthermore, the political construction of criminal law of Rechterlijk Pardon in philosophical, sociological and legal considerations is that Rechterlijk Pardon is motivated by the need to reconstruction the understanding of judges to impose punishment by looking at the severity of the offender action as well as aspects of the needs of society values of justice.